Effect of Clamping Pressure and Temperature on the Performance of a CuCl(aq)/HCl(aq) Electrolyzer. (1st January 2015) - Khurana, Sanchit; Hall, Derek M.; Schatz, Rich S.; Lvov, Serguei N.
Abstract : Changes in the performance of a CuCl(aq)/HCl(aq) electrolytic cell are reported as a function of temperature and the compression pressure applied at the end plates during cell assembly. The pressure applied on the end plates effected the contact resistance, and an optimum compression pressure of 6.3 psi (bolt torque: 20 Nm) showed the best performance. Polarization curves and EIS data were taken at 40, 60, and 80°C to observe the changes in ohmic and nonohmic impedance contributions. A significant increase in the cell performance was observed as the temperature was increased from 40 to 80°C.